MODEL INFORMATION DASHBOARD NILAI SISWA: TOOLS MONITORING HASIL BELAJAR - Husein Muhammad Fahrezy; Toga Parlindungan Silaen; Henderi Henderi (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
In teaching and learning activities it is necessary to have monitoring activities carried out by teachers to the principal, so that the teaching staff know the values and limits of the ability of their students. The process of delivering information about the grades of students to the principal is still manually and less than optimal. So we need a system that makes it easy for teachers to monitor their students. Therefore, the discussion in this paper is to design a dashboard information model that will facilitate collaboration between teachers and monitor the development of students' abilities by the principal. This research uses the needs analysis, planning, prototype design and prototype review methods. So the data displayed will be in accordance with what is needed by the school. With the dashboard information will provide teaching staff information that is as needed, interactive and more efficient.